Baseline and Amphetamine-Stimulated Dopamine Activity Are Related in Drug-Naïve Schizophrenic Subjects - Abi-Dargham, Anissa; van de Giessen, Elsmarieke; Slifstein, Mark; Kegeles, Lawrence S.; Laruelle, Marc (Biological psychiatry (1969), 2009)
Previous studies demonstrated increased striatal dopamine (DA) release after amphetamine challenge and increased striatal baseline occupancy of D2 receptors in patients with schizophrenia compared with control subjects. We report here on the relationship between these two aspects of DA release in drug-naïve patients with schizophrenia (SCZ) and matched healthy control subjects (HC). Six drug-naïve SCZ and eight HC underwent single-photon emission computed tomography (SPECT) scans after bolus followed by constant infusion of (S)-(-)-3-[123I]iodo-2-hydroxy-6-methoxy-N-[(1-ethyl-2-pyrrolidinyl)methyl]benzamide ([123I]IBZM) under three conditions to determine the equilibrium specific to non-displaceable binding potential (BP ND) for striatal D2 at baseline, after amphetamine administration and after DA depletion. Amphetamine induced decrease in BP ND was positively correlated with BP ND increase after DA depletion in SCZ ( p = .02) but not in HC ( p = .44). Additionally, both were significantly increased. In drug-naïve patients with schizophrenia but not in control subjects, stimulated and baseline DA release are both increased and positively correlated. At the neuronal level this association suggests that capacity for storage in presynaptic terminals, measured with the amphetamine paradigm, and baseline intrasynaptic DA release, measured with the α-methyl-para-tyrosine (αMPT) paradigm, are associated in schizophrenia, both consistent with increased midbrain DA cells activity.